Arrestee Drug Abuse Monitoring (ADAM) Program in the United States, 1998 ([Verlag nicht ermittelbar], 1999)
The Arrestee Drug Abuse Monitoring (ADAM) Program measures levels of and trends in drug use among persons arrested and booked in the United States. The ADAM Program is a redesigned version of the Drug Use Forecasting (DUF) Program (DRUG USE FORECASTING IN 24 CITIES IN THE UNITED STATES, 1987-1997 [ICPSR 9477]), upgraded methodologically and expanded to include 35 cities. The data address the following topics: (1) types of drugs used by arrestees (based on self-reports and urinalysis), (2) self-reported dependency on drugs, (3) self-reported need for alcohol/drug treatment, (4) the relationship between drug use and certain types of offenses, and (5) the relationship between self-reported indicators of drug use and indicators of drug use based on urinalysis. Participation in the project is voluntary, and all information collected from the arrestees is anonymous and confidential. The data include the arrestee's age, race, gender, educational attainment, marital status, and the charge at the time of booking. The recently modified ADAM/DUF interview instrument (used for part of the 1995 DUF data and all of the DUF 1996, DUF 1997, and ADAM 1998 data) also collected information about the arrestee's self-reported use of 15 drugs. For each drug type, arrestees were asked whether they had ever used the drug, the age at which they first used the drug, whether they had used the drug within the past three days, how many days they had used the drug within the past month, whether they had ever needed or felt dependent on the drug, and whether they were dependent on the drug at the time of the interview. Data from the new interview instrument also included information about whether arrestees had ever injected drugs and whether they were influenced by drugs when they allegedly committed the crimes for which they were arrested. The data also include information about whether the arrestee had been to an emergency room for drug-related incidents and whether he or she had prior arrests in the last 12 months. Data that continue to be collected with the new version of the ADAM/DUF interview provide information about arrestees' histories of drug/alcohol treatment, including whether they ever received drug/alcohol treatment and whether they needed drug/alcohol treatment. As part of the ADAM program, arrestees were asked to provide a urine specimen, which was screened for the presence of the following ten drug types: marijuana, opiates, cocaine, PCP, methadone, benzodiazepines (Valium), methaqualone, propoxyphene (Darvon), barbiturates, and amphetamines (positive test results for amphetamines were confirmed by gas chromatography).